Imipenem Susceptibility Pattern of Bacterial Isolates on Pregnant Women with Urinary Tract Infection in a Tertiary Hospital - Fatema, Shanaz; Hossain, Mohammad Alamgir; Mamtaz, Syeda Shahnoor Hasina; Chowdhury, Abu Hena Md. Saiful Karim; Hassan, Abdullah Al; Ara, Jahan (IAHS Medical Journal, 2024)
Background: Urinary Tract Infection (UTI) in pregnancy, including Asymptomatic Bacteriuria (ASB) is associated with maternal morbidity and adverse pregnancy outcomes, like preterm birth and low birth weight. In spite of an association of ASB with adverse pregnancy results, screening and treatment is not done with much strength in our country. The antibiotic susceptibility patterns differ from region to region and in different global locations and are found to vary from time to time. This study was done to evaluate the susceptibility pattern of bacterial isolates against Imipenem causing UTI in pregnant women. Materials and methods: This observational study was conducted at the Department of Clinical Pathology, Bangabandhu Memorial Hospital, Chattogram During the period from January to June 2021. Urine sample from a total of 104 pregnant women was enrolled in this study. Isolation and identification of bacteria was done by conventional culture method and Imepenem susceptibility test, by Kirby-Bauer disc diffusion method. Results: Among the study samples, 31(29.8%) showed positive culture result and taken as confirmed UTI. E. coli (45.10%) was the predominant isolated bacteria followed by Klebsiella spp. (25.80%). 90% bacterial isolates were found sensitive to Imipenem and rest 10% were resistant. 93% E. coli showed sensitivity to Imipenem, whereas Klebsiella spp. showed 87.5% and Staphylococcus aureus showed 75% sensitivity to Imipenem. Both Enterococcus spp. and Pseudomonas spp. showed 100% sensitivity to Imipenem. Conclusion: Bacterial resistance against Imipenem is increasing day by day. So it should be kept as a reserve drug for severe life threatening condition. IAHS Medical Journal Vol 6(2), December 2023; 40-43